Assessment literacy components across subject matters - Fatemeh Zolfaghari; Alireza Ahmadi (Cogent Education, 2016)
This study aimed at discovering general and specific assessment literacy components from the perspective of Iranian high school teachers. To this end, 32 humanities, science, English language, and non-English language teachers were interviewed. The interviewees referred to teachers’ ability to identify the worth assessing contents, familiarity with the assessment process, emotional understanding of the learners, and ethical knowledge as the general components of assessment literacy. Regarding the course-specific assessment literacy components, the participants talked of the teachers’ ability to assess the main course contents in that each course has its own exclusive contents. In particular, English language teachers highlighted teachers’ psychological knowledge and science teachers referred to content mastery as other course-specific assessment literacy components. Altogether, it is recommended that teacher training organizations consider these findings in training more qualified teachers as assessors. Further, teachers can consider assessment literacy components to correctly identify learners’ strengths and weaknesses and to assist the students’ future study and job choices.